Factors Related to the Severity of Dengue Infection in Adult Patients Treated at Sanjiwani Regional General Hospital - Ida Bagus Made Agastya Pranata; Saraswati Laksmi Dewi; Putu Aryagiri Prebawa; Komang Trisna Sumadewi (Publication Department, Universitas Warmadewa, 2026)
Dengue infection remains a major global health problem. This study aimed to determine factors associated with the severity of dengue infection among adult patients treated at Sanjiwani Gianyar Regional General Hospital in 2023. An analytical observational study with a cross-sectional design was conducted using consecutive sampling. A total of 100 adult patients with confirmed dengue infection were included. Severity was classified as Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF) based on WHO criteria. Chi-square analysis and crude odds ratio (OR) estimation were performed. Age >60 years was significantly associated with severe dengue (OR = 2.94; 95% CI: 1.25–6.92; p=0.014). Female gender was also associated with higher odds of severe dengue compared to males (OR = 2.33; 95% CI: 1.05–5.15; p=0.039). Secondary infection status showed the strongest association with severity (OR = 5.40; 95% CI: 2.24–13.04; p=0.001). In conclusion, age, gender, and infection status were significantly associated with dengue severity. These findings may assist clinicians in identifying patients who require closer clinical monitoring.